1974
DOI: 10.1161/01.cir.50.5.948
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic Innervation of the Canine and Human Ventricular Conducting System

Abstract: SUMMARYAugmentation of vagal tone increases ventricular fibrillation threshold (VFT) under nonischemic and ischemic conditions and protects against spontaneous ventricular fibrillation during experimental myocardial infarction. The purpose of this study was to identify the anatomic pathways responsible for this cholinergically-mediated enhanced electrical stability and to determine whether or not these pathways are present in human hearts. Rich cholinergic innervation of the sinoatrial node, atrioventricular n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
67
2

Year Published

1982
1982
2004
2004

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(77 citation statements)
references
References 9 publications
8
67
2
Order By: Relevance
“…(7) Atropine was infused at a rate of 12 gg/min. (8) After hemodynamic measurements had been made during atropine infusion, atropine was continued with the concurrent infusion of dobutamine at the rate used for the first dobutamine infusion. (9) After completion of the drug infusions, radiographic contrast was injected to confirm the continued position of the catheter in the left main coronary ostium.…”
Section: Hemodynamic Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…(7) Atropine was infused at a rate of 12 gg/min. (8) After hemodynamic measurements had been made during atropine infusion, atropine was continued with the concurrent infusion of dobutamine at the rate used for the first dobutamine infusion. (9) After completion of the drug infusions, radiographic contrast was injected to confirm the continued position of the catheter in the left main coronary ostium.…”
Section: Hemodynamic Measurementsmentioning
confidence: 99%
“…However, changes in parasympathetic tone can substantially attenuate the positive inotropic response to a variety of sympathetic stimuli in anesthetized2-5 and conscious6,7 dogs, and vagal fibers can be seen to innervate the human left ventricle, albeit to a lesser density than the sinoatrial or atrioventricular nodes. 8 The purpose of this study was to determine whether cholinergic pathways in the human heart modulate basal left ventricular contractility or the positive inotropic response to 8-adrenergic stimulation. Acetylcholine, a cholinergic agonist; atropine, a cholinergic antagonist; and dobutamine, a 3-adrenergic agonist, were infused directly into the left main coronary artery of patients with angiographically normal coronary arteries, and left ventricular peak +dP/dt was measured to assess changes in contractility.9 We studied six subjects with normal left ventricular function and, to address a po-tential action of acetylcholine or atropine to affect cardiac function by modulating presynaptic norepinephrine release, seven subjects who had undergone cardiac transplantation from 1 to 3 years previously.…”
mentioning
confidence: 99%
“…These studies show that in the human and pig heart the left vagus nerve can profoundly decrease the inotropic state of the left ventricular myocardium independent of its bradycardic effect. et al 1974;Loffelholz & Pappano, 1985;Du et al 1995) as well as a dense distribution of muscarinic M 2 receptors (Fields et al 1978;Goyal, 1989;Deighton et al 1990). However, a load-independent assessment of the influences of vagal nerve stimulation on contractility, in mammals other than the dog, is lacking.…”
mentioning
confidence: 99%
“…In humans, there is evidence for an efferent parasympathetic innervation of the LV myocardium (Kent et al 1974) and for the presence of muscarinic M2 cholinoreceptors (Deighton et al 1990). Positron emission tomography with the "C-labelled muscarinic antagonist methiodide quinuclidinyl benzilate has shown that the highest binding density in the human heart is in the ventricular septum and in the left ventricle (Syrota e f al.…”
Section: Vagal Control Of Ventricular Contractilitymentioning
confidence: 99%